Sustained Obesity and Depressive Symptoms over 6 Years: Race by Gender Differences in the Health and Retirement Study - Carter, Julia D.; Assari, Shervin (Frontiers in Aging Neuroscience, 2017)
Background Although obesity and physical activity influence psychosocial well-being, these effects may vary based on race, gender, and their intersection. Using six-year follow-up data of a nationally representative sample of adults over age of 50 in the United States, this study aimed to explore race by gender differences in additive effects of sustained high body mass index (BMI) and physical activity on sustained depressive symptoms (CES-D) and self-rated health (SRH). Methods Data came from waves 7, 8, and 10 (2004 to 2010) of the Health and Retirement Study (HRS), an ongoing national cohort started from 1992. The study enrolled a representative sample of Americans (n= 19,280) over the age of 50. Latent factors were used to calculate sustained high BMI and physical activity (predictors) and sustained poor SRH and high depressive symptoms (outcomes) based on measurements in 2004, 2006, and 2010. Age, education, and income were confounders. Multi-group structural equation modeling (SEM) was used to test the additive effects of BMI and physical activity on depressive symptoms and SRH, where the groups were defined based on race by gender. Results Group differences were apparent in the direction and significance of the association between sustained high BMI and depressive symptoms. The association between sustained high BMI and depressive symptoms was positive and significant for White women (B = 0.03, p = .007) and non-significant for White men (B = -0.03, p = .062), Black men (B = -0.02, p = .564) and Black women (B = 0.03, p = .110). No group differences were found in the paths from sustained physical activity to depressive symptoms, or from physical activity or BMI to SRH. Conclusion Sustained high BMI and high depressive symptoms after age 50 are positively associated only for White women. As the association between sustained health problems such as depression and obesity are not universal across race and gender groups, clinical and public health interventions and programs that simultaneously target multiple health problems may have differential effects across race by gender groups. □